Analysis of Students' Misconceptions in The Exponential Numbers Material in Terms of Concept Understanding Through Four-Tier Diagnostic Tests Based on Gender - Muhammad Zilfikri; Kamid Kamid; Evita Anggereini (Journal of General Education and Humanities, 2026)
Misconceptions are a fundamental problem in mathematics learning because they can hinder students’ understanding of more advanced concepts, particularly in exponentiation. This study aims to describe students’ misconceptions in exponentiation material in terms of conceptual understanding using a four-tier diagnostic test stratified by gender. This research employed a descriptive, qualitative approach. The research subjects were eighth-grade students of SMP Negeri 31 Tanjung Jabung Timur in the odd semester of the 2025/2026 academic year, selected using purposive sampling, namely, students identified as experiencing misconceptions. The research instruments consisted of a four-tier diagnostic test equipped with the Certainty of Response Index (CRI) and semi-structured interview guidelines. Data were analysed by classifying students’ responses into the following categories: conceptual understanding, partial understanding, false understanding (positive and negative), misconceptions, and lack of conceptual understanding. The results showed that 23 of 38 students experienced misconceptions, with a higher proportion among male students than among female students. The identified misconceptions included generalisation, notation, overspecialization, and mathematical language. These findings indicate that gender differences influence students’ tendencies to experience misconceptions in exponentiation material. Therefore, the four-tier diagnostic test is effective for identifying misconceptions in depth and can serve as a basis for teachers to design more appropriate instructional strategies to reduce students’ misconceptions.